Up To No Good - Weber, Carl 1964- (New York : Kensington Pub. Corp., 2009)
There is always a man around the corner. And church trustee James Black should know-- he's usually that very man, carrying on affairs with married women and sleeping with one conquest after another. When the tables are turned, his newfound love generates a ripple effect of shocking proportions...
a"Dafina books."
Keywords: African American men -- Fiction; Man-woman relationships -- Fiction; Domestic fiction